Exploring the nature and synchronicity of early cluster formation in the Large Magellanic Cloud – V. Multiple populations in ancient globular clusters. Issue 2 (28th March 2020) - Gilligan, Christina K; Chaboyer, Brian; Cummings, Jeffrey D; Mackey, Dougal; Cohen, Roger E; Geisler, Douglas; Grocholski, Aaron J; Parisi, M C; Sarajedini, Ata; Ventura, Paolo; Villanova, Sandro; Yang, Soung-Chul; et al.
ABSTRACT: We examine four ancient Large Magellanic Cloud (LMC) globular clusters (GCs) for evidence of multiple stellar populations using the Advanced Camera for Surveys and Wide Field Camera 3 on the Hubble Space Telescope Programme GO-14164. NGC 1466, NGC 1841, and NGC 2257 all show evidence for a redder, secondary population along the main sequence. Reticulum does not show evidence for the presence of a redder population, but this GC has the least number of stars and Monte Carlo simulations indicate that the sample of main-sequence stars is too small to robustly infer whether a redder population exists in this cluster. The second, redder, population of the other three clusters constitutes $\sim 30-40{{\ \rm per\ cent}}$ of the total population along the main sequence. This brings the total number of ancient LMC GCs with known split or broadened main sequences to five. However, unlike for Hodge 11 and NGC 2210 (see Gilligan et al. (2019 )), none of the clusters shows evidence for multiple populations in the horizontal branch. We also do not find evidence of a second population along the red giant branch.